(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
One of the diseases that can cause obstructions in the respiratory tract is Bronchial Asthma. Asthma makes the airways in the lungs narrow due to inflammation and tightening of the muscles around the airways. Inflammation can cause cells in the respiratory tract to produce a lot of secret, as a result air flow can be obstructed in the respiratory tract which causes shortness of breath making it difficult to breathe. When asthmatics feel shortness of breath, there will be an increase in respiratory frequency and a decrease in oxygen saturation. Non-pharmacological therapy methods in the form of breathing techniques can be performed on asthma patients, one of which is the Buteyko Breathing Exercise technique. Buteyko Breathing Exercise technique combines nasal breathing, diaphragm and pause control. The purpose of this study was to determine the stability of Respiratory Rate in patients with Bronchial Asthma after applying Buteyko Breathing Exercise Technique. This research is a descriptive case study with 2 research subjects and was conducted in May 2023. This study uses interview, observation and physical examination techniques in data collection with previously prepared instruments. Data is presented in the form of narratives and tables. The results show that there is a change in Respiratory Rate to be stable in both subjects, with the mode value of Respiratory Rate in the first subject is 18 x/min and the second subject is 20 x/min.